Правові принципи бюджетного контролю - Гетманець, О. П.; Hetmanets, O. P.; Гетманець Ольга Петрівна (Форум права. - 2017. - № 5. - С. 84–90, 2017)
Досліджені правові умови організації бюджетного контролю і визначені загальноправові принципи, принципи фінансового контролю, як вихідні вимоги його проведення. Названі інституційні принципи організації діяльності органів бюджетного контролю.

The article is focused on determining the principles of budgetary control as a kind of financial one, since there are no legal requirements for this control in the current budget law, which is a significant gap in the budget legislation. It has been proved that the organization of budgetary control requires the establishment of the modern legal principles of the authorized controlling subjects’ activities, as the direction of the financial and control activity of the state. The author on the basis of the analysis of theoretical developments in the science of financial and budgetary law, has proved the need to establish general legal principles such as legalness, equality, unity (association) of rights and duties, responsibility, freedom, justice, humanism, democracy within budget activities, in particular control activity, as well as on the basis of the principles of financial control, covering all general principles applicable in financial law and the principles of public financial activity, since the control is carried out within the control activity, which is a type of public financial activity, as well as institutional principles of control in the budget process. The necessity of differentiating the principles of budget control and the principles of responsibility for violations of the budget legislation and determination of the essence of these principles in the current budget law has been defined. It has been clarified that the establishment of the principles of budgetary control, such as completeness, unity, efficiency, effectiveness, fairness and impartiality, subordination and accountability of controlling subjects, reciprocity, publicity and transparency in the certain Article of the Budget Code of Ukraine will provide legalness and meaningfulness to controlling subjects in exercising their authorities. An urgent task is to make appropriate amendments into the budget legislation, which is of crucial importance for the formation of the modern concept of budgetary control, for its regulatory provision and for the organization of effective budget activity.

Рассмотрены правовые условия организации бюджетного контроля и определены общеправовые принципы, принципы финансового контроля, как исходные требования его проведения. Названы институциональные принципы организации деятельности органов бюджетного контроля.
Правовые принципы бюджетного контроля
Legal Principles of Budgetary Control
Keywords: Фінансове право. Бюджетне право. Банківське право. Financis Law. Budget Law. Banking Law. Финансовое право. Бюджетное право. Банковское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; принципи права; бюджетний контроль; фінансовий контроль; бюджетна система; бюджетний процес; бюджетний контроль; фінансова відповідальність; принципы права; бюджетный контроль; финансовый контроль; бюджетная система; бюджетный процесс; финансовая ответственность; principles of law; budgetary control; financial control; budget system; budget process; financial liability